2005
DOI: 10.1007/s00198-004-1802-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of risedronate on trabecular microstructure and biomechanical properties in ovariectomized rat tibia

Abstract: We determined the effect of risedronate on the trabecular microstructure of ovariectomized rat tibiae, using micro-computed tomography, in order to investigate how changes in microstructure contribute to biomechanical properties. Fifty 18-week-old rats underwent sham operation (n=10) or ovariectomy (OVX) (n=40). The OVX rats were further divided into four groups (n=10 for each group) and treated with risedronate at doses of 0, 0.1, 0.5 or 2.5 mg/kg for 9 months. OVX caused deterioration of three-dimensional tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 19 publications
6
33
1
Order By: Relevance
“…Previous studies have reported that plate perforations without loss of trabecular elements tend to artificially increase connectivity (Borah et al, 2004), and this may explain why the connectivity density for the control bone tended to be higher than the suppressed bone in this study. The trends in architectural changes due to suppressed bone turnover are also consistent with previous clinical (Borah et al, 2004) and pre-clinical (Ito et al, 2005;Muller et al, 2004) studies which have shown that antiresorptive treatment preserves the trabecular architecture.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies have reported that plate perforations without loss of trabecular elements tend to artificially increase connectivity (Borah et al, 2004), and this may explain why the connectivity density for the control bone tended to be higher than the suppressed bone in this study. The trends in architectural changes due to suppressed bone turnover are also consistent with previous clinical (Borah et al, 2004) and pre-clinical (Ito et al, 2005;Muller et al, 2004) studies which have shown that antiresorptive treatment preserves the trabecular architecture.…”
Section: Discussionsupporting
confidence: 89%
“…While the effects of suppressed bone turnover on the mineralization and the organic component of the trabecular tissue, and trabecular microarchitecture have been investigated through a number of clinical (Boivin et al, 2000;Borah et al, 2004;Borah et al, 2005;Roschger et al, 2001) and pre-clinical studies (Allen et al, 2006a;Allen et al, 2006b;Day et al, 2004;Ding et al, 2003;Ito et al, 2005;Mashiba et al, 2001;Muller et al, 2004), the independent contribution of suppression-induced microarchitectural changes alone to the improved mechanical properties remain unclear. Analysis of simulated microarchitectural changes have shown that inhibition of trabecular perforation (Guo and Kim, 2002;Riggs and Melton, 2002) and filling in of the remodeling space Parfitt, 2002) may have a disproportionate effect on trabecular bone strength compared to the accompanying changes in bone volume fraction, particularly for low-density bone.…”
Section: Introductionmentioning
confidence: 99%
“…Oral dose rates of 0.5 and 2.5 mg/kg risedronate prevented bone loss in an ovariectomy model in rats while 0.1 mg/kg had no effect. 27 Reported results of pre-clinical testing for risedronate suggest that the dose rate needed in a rat to be equivalent to the standard 35 mg/kg/week human dose is 0.5 mg/kg. a Bone resorption along the stress fracture line was clearly depressed by treatment with risedronate.…”
Section: Discussionmentioning
confidence: 99%
“…24 Moreover, mFEA of excised bones is non-destructive allowing for subsequent histological analysis. Although a number of studies involving rodents have used mFEA to determine the effect of drug treatment on bone strength, [25][26][27][28][29][30] there is little evidence in the literature establishing that mFEA can accurately predict the mechanical properties of rodent bone, and especially murine bones. Of the few studies comparing FEA predictions to experimental measurements of strength in rodent tissues, long bones were tested with limited examination of material definitions.…”
Section: Introductionmentioning
confidence: 99%